Beragama Katolik, Berbudaya Tionghoa sebuah Kajian Terhadap Hibriditas Umat Katolik-Tionghoa Paroki St. Maria Immaculata Slawi - Julianto, Romario; Lelono, Martinus Joko (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Santa Maria Immaculata Slawi Parish stands in the Tegal Regency area which has a history of the development of the Chinese community. Chinese ethnicity plays an important role in the dynamics of the Parish. They simultaneously live Chinese culture and the Catholic faith. As a result of the New Order policies they were unable to live out their culture, but Presidential Decree Number 6 of 2000 and Presidential Decree Number 19 of 2000 opened up space for their cultural expression. On Chinese New Year they start holding toa pek kong or tepekong mutual carnivals. The gotong tepekong ritual is a procession of palanquins containing statues of ancestors that are paraded around the city. This article will explore the appreciation of Chinese Catholics in living out two different traditions. Homi K. Bhabha's thoughts are used to understand the attitude choices of the Chinese-Catholic community in Slawi. In his study, Homi K. Bhabha talks about